ANALISIS BAHASA DAN KUASA IDEOLOGI DALAM PERNYATAAN PRESIDEN PRABOWO: "WARGA DESA TIDAK PAKAI DOLAR” - Muhammad Rayhan Kurniawan; Angga Nurhidayat; Rifma Ghulam Dzaljad (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
President Prabowo Subianto’s statement that “people in villages don’t use dollars” amid the rupiah’s depreciation to Rp17,600 per USD has sparked public controversy. This study critically analyzes the discourse using Norman Fairclough’s Critical Discourse Analysis (CDA) framework, which comprises three interrelated dimensions: textual analysis, discursive practice, and sociocultural practice. The research aims to reveal how language functions as a mechanism for reproducing power and political ideology that marginalizes rural communities. Findings demonstrate that the statement employs economic simplification that obscures the indirect impacts of rupiah depreciation on rural Indonesia, including rising import-driven inflation and increased prices for fertilizers, fuel, animal feed, and medicines. Ideologically, the discourse reproduces an oppositional binary between a “carefree” political elite and “untouched” villagers, while naturalizing the notion that rural populations remain unaffected by macroeconomic policies. The study concludes that presidential language is not neutral; rather, it carries ideological messages that sustain dominant power structures through discursive simplification and the naturalization of inequality.